The stability of self-reported adverse experiences in childhood: a longitudinal study on obesity - Silva, Susana Sofia Pereira da (2013)
The literature on the effect of maltreatment has revealed several methodological problems of retrospective studies, such as the validity and stability of retrospective reports, which may be influenced by factors such as one's mental health at the time of the report. This study aims to assess the temporal stability of self-reported adverse childhood experiences at three different time points, separated by 6 months each, and to analyze the relationship between general psychopathology and the number of reported experiences. Thirty obese participants responded to the Portuguese version of the Childhood History Questionnaire, a self-report measure that assesses adverse childhood experiences, and the Brief Symptom Inventory. The results suggest that adverse childhood experiences are common in these participants (time 1: = 1.87, SD = 1.3; time 2: = 1.98, SD = 1.6; time 3: = 1.98, SD = 1.6). The agreement levels, as measured by kappa values, were satisfactory for the dimensions of maltreatment focused on the individual, with kappas ranging between .34 and .44. Our participants did not exhibit psychopathology at any of the time points, and the psychopathological symptoms were not related to total adversity reported. The major contribution of this study is the comparison of self-reports at three time points, separated by significant time intervals, and the inclusion of 10 different dimensions of childhood adversity. The data show an adequate stability in the report of maltreatment toward the individual (abuse and physical neglect) and in specific aspects of adversity in the family.